1992
DOI: 10.1073/pnas.89.20.9671
|View full text |Cite
|
Sign up to set email alerts
|

Quinolone binding to DNA is mediated by magnesium ions.

Abstract: The binding of plasmid DNA to norfloxacin, a quinolone antibacterial agent, was investigated by fluorescence, electrophoretic DNA unwinding, and affinity chromatography techniques. The amount of quinolone bound to DNA was modulated by the concentration of Mg2+. No interaction was evident in the absence of Mg2+ or in the presence of an excess of Mg2+, whereas maximum binding was observed at a Mg2+ concentration of 1-2 mM. The experimental data can be fitted to the formation of three types of Mg adducts: a binar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(89 citation statements)
references
References 30 publications
3
83
0
1
Order By: Relevance
“…Detailed studies on the molecular mechanism of the action of these antimicrobial agents on bacterial DNA have shown that they bind to the gyrase-associated nucleic acid via a magnesium ion (22). This finding suggests that, in general, quinolones must have a pronounced affinity for magnesium ions to exhibit antibacterial activity.…”
Section: Discussionmentioning
confidence: 95%
“…Detailed studies on the molecular mechanism of the action of these antimicrobial agents on bacterial DNA have shown that they bind to the gyrase-associated nucleic acid via a magnesium ion (22). This finding suggests that, in general, quinolones must have a pronounced affinity for magnesium ions to exhibit antibacterial activity.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the drug was shown to preferentially bind to the single-stranded DNA. Next, the DNA binding was shown to be dependent on the concentration of Mg 2ϩ (46). Subsequent surface plasmon resonance studies on FQ-DNA interaction using single-stranded DNA showed a sequence-dependent binding with high affinity, whereas double-stranded DNA binding seemed to be sequence independent (40).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] None of the models described is completely satisfactory, so new experimental and theoretical contributions will be of value to explain their molecular mechanism of action. Some of the existing theories propose the formation of dimers and tetramers of FQ molecules, that of Shen et al being the first and still one of the most widely accepted theories.…”
Section: )mentioning
confidence: 99%